2020
DOI: 10.1111/weng.12504
|View full text |Cite
|
Sign up to set email alerts
|

World Englishes in the Middle East and North Africa (MENA)

Abstract: This special issue highlights the importance of world Englishes research in the Arabic‐speaking and non‐Arabic Middle East and North Africa (MENA) region. Scrutiny of the world Englishes (WE) research literature suggests that the MENA region is largely understudied and undertheorized, and that there is a lacuna in research with reference to this topic. The use of English in this geopolitical region is diverse, and the spread of English has emerged not merely as a response to political and economic advancements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In addition, there has been a growing scholarship in World Englishes in Arabian Gulf in recent years. The status of English in the Arabian Gulf was investigated and analyzed by many researchers such as Elyas and Mahboob (2021a), Hillman et al (2021), Hopkyns et al (2021), Siemund et al (2021), Tuzlukova and Mehta (2021), and van den Hoven and Carroll (2021). A recent bibliography of World Englishes in the Middle East and North Africa (MENA) has been documented by Elyas and Mahboob (2021b) stressing the importance of World Englishes by current research interests in the region.…”
Section: Saudi Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there has been a growing scholarship in World Englishes in Arabian Gulf in recent years. The status of English in the Arabian Gulf was investigated and analyzed by many researchers such as Elyas and Mahboob (2021a), Hillman et al (2021), Hopkyns et al (2021), Siemund et al (2021), Tuzlukova and Mehta (2021), and van den Hoven and Carroll (2021). A recent bibliography of World Englishes in the Middle East and North Africa (MENA) has been documented by Elyas and Mahboob (2021b) stressing the importance of World Englishes by current research interests in the region.…”
Section: Saudi Englishmentioning
confidence: 99%
“…Saudi English (SE) is an emerging variety of English (Al-Rawi, 2012;Mahboob and Elyas, 2014;Fallatah, 2017;Elyas et al, 2021) that has not been well-researched and mostly investigated from a pedagogical perspective, where grammatical errors in English have been the focus rather than investigating them as features. However, few recent studies on SE were published within the World Englishes framework (Al-Rawi, 2012;Mahboob, 2013;Mahboob and Elyas, 2014;Fallatah, 2017;Bukhari, 2019;Elyas and Mahboob, 2021a;Elyas et al, 2021), but there is still a gap in the literature and more studies on SE are needed. This study hopes to contribute to SE literature by identifying its syntactic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Still, many teachers are concerned about how to incorporate these dimensions into ELT (Dogancay-Aktuna & Hardman, 2018;Rajprasit, 2021;Wang et al, 2021) and into the Saudi context specifically (Bukhari, 2019). Although research in Global Englishes is established in European and Asian region, recent studies have reported the scarcity of Global Englishes-related research in the conservative context of Saudi Arabia (Bukhari, 2019;Elyas & Mahboob, 2020;Elyas et al, 2021). The present study fills this gap in the literature, provides new understanding and contributes to the future development of Global Englishes research and pedagogy.…”
Section: Introductionmentioning
confidence: 64%
“…a powerful carnivore gobbling up the other denizens of the academic linguistic grazing grounds” (Swales, 1997, p. 374), the preeminence of English as the vehicular lingua franca for discipline-specific publication is self-evident. Therefore, English is considered the primary language for research publication in MENA regions (Abdeljaoued & Labassi, 2020; Elyas & Mahboob, 2020).…”
Section: Introductionmentioning
confidence: 99%